A study on ocular manifestations in patients with Diabetes mellitus - Prabhakar Nirmala; Selva Sundari (International Journal of Medical Research and Review, 2016)
Background: Ocular complications other than Diabetic Retinopathy are frequent among diabetic population. This includes diseases causing reversible and irreversible visual loss.Aim: The aim of this study is to find out the frequency of occurrence of different ocular manifestation in patients with diabetes mellitus.Design: Hospital based cross – sectional study on diabetic patients visiting the outpatient department of ophthalmology.Materials and methods: A total number of 820 patients of non insulin dependent diabetes mellitus (NIDDM) and insulin dependent diabetes mellitus (IDDM) were included in this study. Ocular examination included oblique illumination study and slit lamp examination for all patients. Visual acuity was recorded using Snellen’s chart and intraocular pressure was measured using Gold man aplanation tonometer. A-Scan, fluorescein angiography and field charting using automated perimetry were done in selected cases. The results were recorded in a separate proforma for convenience of analysis.Results and conclusion: Our study showed cataract as the most common ocular manifestation in patients with diabetes mellitus (DM) followed by diabetic retinopathy. Development of diabetic retinopathy is directly proportional to the duration of the disease. The frequency of occurrence of various manifestations is similar to that of studies conducted worldwide.